PENETAPAN KADAR KURKUMINOID DALAM SEDIAAN SIRUP TEMULAWAK (Curcuma xanthorizzha Roxb) DENGAN SPEKTROFOTOMETRI - R Herni Kusriani (JURNAL FARMASI GALENIKA, 2014)
Curcuminoid is the compound contained in temulawak(Curcumaxanthorizzha Roxb). Some research reports indicate that curcumin has various pharmacological activities such as hepatoprotector, anti-inflammatory, antibacterial, antioxidant, and etc. Study on thedetermination of curcuminoid using visible spectrophotometer was done to find outthe content of curcuminoid in 5sample temulawak syrup(Curcumaxanthorizzha Roxb) on the market. Measurements performed at wavelength of 425nm.The results showed that the limits of detection and quantitation of analytical methods were 0.27 and 0.91ppmand the percentage of recoverywas94.05% Â±0.97%. The content of curcuminoid in 5 samples were350 ppm,347 ppm; 308 ppm; 163 ppm; dan 359 ppm.